Variable Evaluation Costs and the Design of Fallible Hierarchies and Polyarchies - Koh, Winston T. H. (Institutional Knowledge at Singapore Management University, 1992)
We show that when there are variable evaluation costs, the optimal screening standards in a hierarchy (polyarchy) should become less (more) stringent at higher levels. Also, simple reorganization of the optimal hierarchy or polyarchy may not improve net profits, although results from information theory show that gross profits can be increased.